PRAKTIK YOGA ASANAS DALAM MENINGKATKAN DAYA KOGNITIF SISWA SEBAGAI IMPLEMENTASI PENDIDIKAN KARAKTER - Ni Putu Eni Astuti; Putu Beny Pradnyana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to describe the shift of cognitive power and the reinforcement of characters by yoga asanas practice. This study was a qualitative descriptive study involving the students of SDN 2 Sesetan, Denpasar, Bali. The data were collected through interview and observation. Then, the data were analyzed based on the results of observation related to the students’ learning concentration and character reinforcement during yoga extracurricular activities as well as from the analysis of interview related to the systematic and materials of yoga asanas. Findings of this study revealed that (1) yoga asanas could improve one of the cognitive functions, i.e. students’ learning concentration for as much as 71%, (2) yoga asanas strengthened the students’ character, especially the main character aspects, such as independent, religious, and integrity for as much as 85%, and (3) the type of yoga taught was hatta yoga in which the main materials were pavanamuktasana I, hamsa, asana (surya namaskara and chandra namaskara) and acro yoga; these included the steps starting from prayer, asana stretching, the core of asana, asana relaxation, pranayama, and simple meditation.